Africa and the idea of international society - Spies, Yolanda K. (Faculty of Humanities, University of the Free State, 2016)
The shared interests and values of sovereign states prompt them to commit to common rules, conventions and institutions within an inter-subjective “society”, where diplomacy is used as main currency. The idea of international society is, however, not unequivocal. Diversification of the identities and interests of an enlarging pool of states – after the Second World War, mostly contributed by Africa – undermines consensus on the rules of engagement. This is aggravated by the history of the aggressive expansion of international society from its traditional European base. African states have generally embraced the traditional norms (such as sovereignty and non-intervention) of international society, but the continent’s particular history has informed its inclination to use collective diplomacy (multilateralism) to challenge the structure of a deeply asymmetrical international system. In the process, the parochial part of international society that Africa represents has managed to export certain norms to the “older” members of the society. Of special note is the continent’s insistence on horizontal, rather than vertical cooperative relationships, and the fact that development per se has become a fixture on the global diplomatic agenda. The architecture of contemporary universal international society is much more complex and nuanced than ever before, and the role of a sub-society such as Africa – not just in relating to international society, but also in shaping it – is the focus of this article.
Keywords: Africa; Diplomacy; International society; Norms; Values; Development; Post-colonial